Immunotherapy in Recurrent/Metastatic Squamous Cell Carcinoma of the Head and Neck - Hsieh, Ronan W.; Borson, Steven; Tsagianni, Anastasia; Zandberg, Dan P. (Frontiers in Oncology, 2021)
Head and neck cancer is the 6th most common cancer worldwide with the most common histology being squamous cell carcinoma (HNSCC). While the majority of patients present at a stage where curative intent therapy is possible, when patents recur and/or develop metastatic disease outcomes are generally poor, especially with systemic therapy alone, and they lag behind other solid tumors. Over the last decade immunotherapy has revolutionized the field of oncology and anti-PD-1 based therapy has changed the standard of care in recurrent/metastatic (R/M) HNSCC as well. With these gains have come new questions to continue to move the field forward. In this review, we discuss the tumor immune microenvironment and predictive biomarkers, and current status and future directions for immunotherapy in recurrent/metastatic head and neck cancer.